Phenylazo group grafted polyhydroxy graphene oxide-based material and application thereof in electromagnetic wave absorption
By introducing benzazo groups on the surface of polyhydroxy graphene oxide, the impedance matching is coordinated, and the impedance mismatch problem caused by pure graphene due to high conductivity is solved, and efficient electromagnetic wave absorption performance is achieved.
Patent Information
- Application Number
- CN202510046616.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-13
Smart Images

Figure CN119822363A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to a wave absorbing material, in particular to a polyhydroxy graphene oxide-based material grafted with a phenylazo group and application thereof in electromagnetic wave absorption. Background technology:
[0002] The rapid development of electronic communication technology has made electromagnetic radiation pollution a major environmental problem recognized by the world. A large amount of electromagnetic radiation will not only damage precision electronic equipment, but also pose a huge threat to human health. Therefore, it is imperative to develop absorbing materials with characteristics such as light weight, high microwave absorptivity, thin matching thickness and wide absorption bandwidth. Two-dimensional materials, especially graphene, have gradually become one of the most attractive candidate materials due to their excellent chemical and physical properties, such as low density, large specific surface area, high electron mobility, good thermal stability and corrosion resistance. However, the impedance mismatch problem caused by the high conductivity of pure graphene weakens its electromagnetic wave absorption ability. Therefore, regulating the conductivity to coordinate the impedance is the key research direction for the development of efficient graphene-based absorbing materials. Taking advantage of the adjustable dielectric properties of graphene oxide and reduced graphene oxide, it can be functionalized by chemically reacting with the oxygen-containing functional groups on its surface to improve the above problems.
[0003] Studies have shown that the electronic structure and transport properties of graphene-based materials can be changed by covalent modification of functional groups. Due to their chemical stability and rapid response, azo compounds have great potential in enhancing the photoelectric properties of graphene derivatives and help improve the electromagnetic wave absorption performance of graphene-based materials. However, there is currently no mature technology to obtain polyhydroxy graphene oxide-based materials that can absorb electromagnetic waves. Summary of the invention:
[0004] In order to solve the problems existing in the prior art, the present invention provides a polyhydroxy graphene oxide-based material grafted with a phenylazo group and its application in electromagnetic wave absorption.
[0005] The specific technical solutions of the present invention are as follows:
[0006] A polyhydroxy graphene oxide-based material grafted with a phenylazo group, the preparation method of the material is as follows:
[0007] Step 1, adding an aniline compound to a dilute hydrochloric acid solution, heating until completely dissolved, and then cooling under low temperature conditions;
[0008] Step 2, adding a sodium nitrite solution dropwise to the solution prepared in step 1, adding urea to remove excess sodium nitrite after sufficient reaction under low temperature conditions, stirring, and obtaining a diazonium salt;
[0009] Step 3, taking the polyhydroxy graphene oxide suspension, and adjusting the pH to 8-10 with an alkaline buffer;
[0010] Step 4, adding the diazonium salt prepared in step 2 to the suspension prepared in step 3, and continuing stirring at low temperature to carry out coupling reaction;
[0011] Step 5, after the coupling reaction is completed, filtering, washing, and vacuum drying are performed to obtain a polyhydroxy graphene oxide-based material grafted with a phenylazo group;
[0012] In the above steps, the molar ratio of the aniline compound, sodium nitrite and dilute hydrochloric acid is 1:(1.05-1.15):(2.5-5.5); the molar ratio of the aniline compound to the polyhydroxy graphene oxide is 200:1.
[0013] The present invention is further designed that in step 1, the aniline compound is p-bromoaniline, p-chloroaniline or p-trifluoromethylaniline.
[0014] A further design is that the low temperature condition is an ice water bath at 0 to 5°C.
[0015] A further design is that in step 4, the coupling reaction time is 4 to 7 hours.
[0016] A further design is that in step 1, the concentration of the dilute hydrochloric acid is 4 to 6 mol / L.
[0017] A further design is that in step 3, the polyhydroxy graphene oxide suspension is prepared by the following method:
[0018] 1) dispersing graphene oxide in DMSO, adding manganese acetate as a catalyst, stirring evenly to form a suspension, and adjusting the pH to 4 with a dilute hydrochloric acid solution;
[0019] 2) irradiating the suspension with ultraviolet light for 8 days, adding ZnO and isopropanol, and continuing to irradiate under ultraviolet light for 8 days to obtain a polyhydroxy graphene oxide suspension.
[0020] A further design is that in step 3, the alkaline buffer solution is a buffer solution prepared from sodium carbonate and sodium bicarbonate.
[0021] A further design is that in step 4, after the coupling reaction, an appropriate amount of dilute hydrochloric acid is added, the temperature is raised and stirring is continued, and excess alkaline buffer is removed until the pH value is 7; then the temperature is raised to 50°C, stirring is continued for 4 hours, and by-products are removed.
[0022] A further design is that in step 5, the vacuum drying temperature is 80-120° C. and the time is 48 hours.
[0023] The application of the above-mentioned polyhydroxy graphene oxide-based material grafted with phenylazo groups in microwave absorption.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention uses aniline compounds and polyhydroxy graphene oxide as raw materials, and synthesizes a polyhydroxy graphene oxide-based absorbing material grafted with a phenylazo group by a diazo coupling method, and verifies the feasibility of the preparation method by spectral characterization, that is, the feasibility of coordinating impedance matching by a modification method of covalently grafted functional groups. The preparation method is simple, low-cost and high-yield.
[0026] (2) Graphene-based materials can cause impedance mismatch due to their high conductivity. The absorbing material provided by the present invention introduces a phenylazo group on the surface of the graphene-based material. The phenylazo group itself is a non-conductive group. After being grafted onto the graphene-based material, it will interrupt the original electron transmission path of the graphene, increase the resistance to electron movement, thereby reducing the conductivity of the material and coordinating impedance matching. At the same time, the steric hindrance effect generated by the introduction of the phenylazo group can reduce the efficiency of electron transmission and effectively limit the conductive network, thereby optimizing impedance matching.
[0027] (3) The polyhydroxy graphene oxide-based microwave absorbing material grafted with azo groups provided by the present invention can dissipate electromagnetic waves through various mechanisms such as polarization loss, multiple reflections and scattering between layers, and conduction loss, and exhibits good microwave absorbing performance. This provides a feasible technology for the development of lightweight, efficient, and stable electromagnetic microwave absorbing materials.
[0028] (4) The present invention reasonably selects the coupling reaction time, the molar ratio of the aniline compound to dilute hydrochloric acid, and the molar ratio of the aniline compound to sodium nitrite, thereby ensuring the yield of the product and facilitating mass industrial production.
[0029] (5) The present invention reasonably adjusts the pH range of the polyhydroxy graphene oxide suspension to 8 to 10. When the pH of the suspension is lower than 8, the phenolic hydroxyl group cannot form phenoxy anions, and the reaction rate is slow or even cannot proceed. When the pH of the suspension is higher than 10, the diazonium salt reacts with the OH - A reaction occurs to generate diazo acid or diazo acid anion, causing it to lose its coupling ability and reduce the reaction yield. Description of the drawings:
[0030] Figure 1 Schematic diagram of the synthesis route of the polyhydroxy graphene oxide-based microwave absorbing material grafted with phenylazo groups prepared in an embodiment of the present invention;
[0031] Figure 2 FT-IR spectrum of the polyhydroxy graphene oxide-based absorbing material grafted with phenylazo groups prepared in an embodiment of the present invention;
[0032] Figure 3 This is an XRD spectrum of the polyhydroxy graphene oxide-based absorbing material grafted with phenylazo groups prepared in an embodiment of the present invention;
[0033] Figure 4 The reflection loss and impedance matching and frequency correlation spectrum of the annular test sample made of the polyhydroxy graphene oxide-based absorbing material grafted with phenylazo groups prepared in the embodiment of the present invention. Specific implementation method:
[0034] The present invention will be further described below in conjunction with examples:
[0035] Preparation of polyhydroxy graphene oxide suspension:
[0036] Polyhydroxy graphene oxide is a type of graphene oxide, and its preparation process is as follows:
[0037] 1) Graphene oxide (0.4 g) was dispersed in dimethyl sulfoxide (DMSO) (200 mL), manganese acetate was added as a catalyst, and the mixture was stirred to form a suspension, and the pH value was adjusted to 4 with a dilute hydrochloric acid solution.
[0038] 2) The suspension was irradiated with ultraviolet light (λ=185 nm) for 8 days, ZnO and isopropanol were added, and the suspension was irradiated with ultraviolet light (λ=185 nm) for another 8 days to obtain a polyhydroxy graphene oxide suspension, which was used in the following examples.
[0039] Example 1.
[0040] (1) Add p-bromoaniline (1.03 g, 6 mmol) to a dilute hydrochloric acid solution (6 mL, 4 mol / L), heat to completely dissolve the p-bromoaniline, and then cool the solution in an ice-water bath (0-5°C).
[0041] (2) Dissolve sodium nitrite (0.46 g, 6.6 mmol) in 4 mL of water to obtain an aqueous solution of sodium nitrite, slowly dropwise add the aqueous solution of sodium nitrite to the solution obtained in step 1, and stir in an ice-water bath for 30 minutes. Then add urea (10 mg, 0.2 mmol) to remove excess sodium nitrite, and continue stirring for 10 minutes to obtain a diazonium salt solution.
[0042] (3) Add polyhydroxy graphene oxide suspension (150 mL) into a three-necked flask, dissolve sodium bicarbonate (0.42 g, 5 mmol) and sodium carbonate (0.20 g, 2 mmol) in water (50 mL) to prepare an alkaline buffer solution to adjust the pH of the suspension, and place it in an ice water bath and stir. The molar ratio of p-bromoaniline to polyhydroxy graphene oxide is 200:1.
[0043] (4) The prepared diazonium salt solution was slowly added dropwise to the above suspension, and the mixture was stirred in an ice-water bath for 4 hours to carry out the coupling reaction. Dilute hydrochloric acid was added to remove the excess sodium bicarbonate and sodium carbonate until the pH value was 7, and then the temperature was raised to 50° C. and the mixture was stirred for 4 hours to remove the by-products.
[0044] (5) After the reaction is completed, the system is cooled to room temperature, filtered, washed with water, and vacuum dried at 80° C. for 48 hours to obtain the product p-bromophenylazo-grafted polyhydroxy graphene oxide (0.25 g).
[0045] Example 2.
[0046] (1) Add p-bromoaniline (1.03 g, 6 mmol) to a dilute hydrochloric acid solution (8.25 mL, 4 mol / L), heat to completely dissolve the p-bromoaniline, and then cool the solution in an ice-water bath (0-5°C).
[0047] (2) Dissolve sodium nitrite (0.46 g, 6.6 mmol) in 4 mL of water to obtain an aqueous solution of sodium nitrite, slowly dropwise add the aqueous solution of sodium nitrite to the solution obtained in step 1, and stir in an ice-water bath for 30 minutes. Then add urea (10 mg, 0.2 mmol) to remove excess sodium nitrite, and continue stirring for 10 minutes to obtain a diazonium salt solution.
[0048] (3) Add polyhydroxy graphene oxide suspension (150 mL) into a three-necked flask, dissolve sodium bicarbonate (0.42 g, 5 mmol) and sodium carbonate (0.20 g, 2 mmol) in water (50 mL) to prepare an alkaline buffer solution to adjust the pH of the suspension, and place it in an ice water bath and stir. The molar ratio of p-bromoaniline to polyhydroxy graphene oxide is 200:1.
[0049] (4) The prepared diazonium salt solution was slowly added dropwise to the above suspension, and the mixture was stirred in an ice-water bath for 4 hours to carry out the coupling reaction. Dilute hydrochloric acid was added to remove the excess sodium bicarbonate and sodium carbonate until the pH value was 7, and then the temperature was raised to 50° C. and the mixture was stirred for 4 hours to remove the by-products.
[0050] (5) After the reaction is completed, the system is cooled to room temperature, filtered, washed with water, and vacuum dried at 80° C. for 48 hours to obtain the product p-bromophenylazo-grafted polyhydroxy graphene oxide (0.23 g).
[0051] Example 3.
[0052] (1) Add p-bromoaniline (1.03 g, 6 mmol) to a dilute hydrochloric acid solution (3.75 mL, 4 mol / L), heat to completely dissolve the p-bromoaniline, and then cool the solution in an ice-water bath (0-5°C).
[0053] (2) Dissolve sodium nitrite (0.46 g, 6.6 mmol) in 4 mL of water to obtain an aqueous solution of sodium nitrite, slowly dropwise add the aqueous solution of sodium nitrite to the solution obtained in step 1, and stir in an ice-water bath for 30 minutes. Then add urea (10 mg, 0.2 mmol) to remove excess sodium nitrite, and continue stirring for 10 minutes to obtain a diazonium salt solution.
[0054] (3) Add polyhydroxy graphene oxide suspension (150 mL) into a three-necked flask, dissolve sodium bicarbonate (0.42 g, 5 mmol) and sodium carbonate (0.20 g, 2 mmol) in water (50 mL) to prepare an alkaline buffer solution to adjust the pH of the suspension, and place it in an ice water bath and stir. The molar ratio of p-bromoaniline to polyhydroxy graphene oxide is 200:1.
[0055] (4) The prepared diazonium salt solution was slowly added dropwise to the above suspension, and the mixture was stirred in an ice-water bath for 4 hours to carry out the coupling reaction. Dilute hydrochloric acid was added to remove the excess sodium bicarbonate and sodium carbonate until the pH value was 7, and then the temperature was raised to 50° C. and the mixture was stirred for 4 hours to remove the by-products.
[0056] (5) After the reaction is completed, the system is cooled to room temperature, filtered, washed with water, and vacuum dried at 80° C. for 48 hours to obtain the product p-bromophenylazo-grafted polyhydroxy graphene oxide (PBPA-MHGO, 0.22 g).
[0057] It can be seen from Examples 1-3 that when the molar ratio of p-bromoaniline to dilute hydrochloric acid is 1:2.5-5.5, the mass of the product first increases and then decreases. Therefore, the following examples will be described based on a molar ratio of p-bromoaniline to dilute hydrochloric acid of 1:4.
[0058] Example 4.
[0059] (1) Add p-bromoaniline (1.03 g, 6 mmol) to a dilute hydrochloric acid solution (6 mL, 4 mol / L), heat to completely dissolve the p-bromoaniline, and then cool the solution in an ice-water bath (0-5°C).
[0060] (2) Dissolve sodium nitrite (0.46 g, 6.6 mmol) in 4 mL of water to obtain an aqueous solution of sodium nitrite, slowly dropwise add the aqueous solution of sodium nitrite to the solution obtained in step 1, and stir in an ice-water bath for 30 minutes. Then add urea (10 mg, 0.2 mmol) to remove excess sodium nitrite, and continue stirring for 10 minutes to obtain a diazonium salt solution.
[0061] (3) Add polyhydroxy graphene oxide suspension (150 mL) into a three-necked flask, dissolve sodium bicarbonate (0.42 g, 5 mmol) and sodium carbonate (0.20 g, 2 mmol) in water (50 mL) to prepare an alkaline buffer solution to adjust the pH of the suspension, and place it in an ice water bath and stir. The molar ratio of p-bromoaniline to polyhydroxy graphene oxide is 200:1.
[0062] (4) The prepared diazonium salt solution was slowly added dropwise to the above suspension, and the mixture was stirred in an ice-water bath for 4 hours to carry out the coupling reaction. Dilute hydrochloric acid was added to remove the excess sodium bicarbonate and sodium carbonate until the pH value was 7, and then the temperature was raised to 50° C. and the mixture was stirred for 4 hours to remove the by-products.
[0063] (5) After the reaction is completed, the system is cooled to room temperature, filtered, washed with water, and vacuum dried at 80° C. for 48 hours to obtain the product p-bromophenylazo-grafted polyhydroxy graphene oxide (PBPA-MHGO, 0.23 g).
[0064] Example 5.
[0065] (1) Add p-bromoaniline (1.03 g, 6 mmol) to a dilute hydrochloric acid solution (6 mL, 4 mol / L), heat to completely dissolve the p-bromoaniline, and then cool the solution in an ice-water bath (0-5°C).
[0066] (2) Dissolve sodium nitrite (0.46 g, 6.6 mmol) in 4 mL of water to obtain an aqueous solution of sodium nitrite, slowly dropwise add the aqueous solution of sodium nitrite to the solution obtained in step 1, and stir in an ice-water bath for 30 minutes. Then add urea (10 mg, 0.2 mmol) to remove excess sodium nitrite, and continue stirring for 10 minutes to obtain a diazonium salt solution.
[0067] (3) Add polyhydroxy graphene oxide suspension (150 mL) into a three-necked flask, dissolve sodium bicarbonate (0.42 g, 5 mmol) and sodium carbonate (0.20 g, 2 mmol) in water (50 mL) to prepare an alkaline buffer solution to adjust the pH of the suspension, and place it in an ice water bath and stir. The molar ratio of p-bromoaniline to polyhydroxy graphene oxide is 200:1.
[0068] (4) The prepared diazonium salt solution was slowly added dropwise to the above suspension, and the mixture was stirred in an ice-water bath for 4 hours to carry out the coupling reaction. Dilute hydrochloric acid was added to remove the excess sodium bicarbonate and sodium carbonate until the pH value was 7, and then the temperature was raised to 50° C. and the mixture was stirred for 4 hours to remove the by-products.
[0069] (5) After the reaction is completed, the system is cooled to room temperature, filtered, washed with water, and vacuum dried at 80° C. for 48 hours to obtain the product p-bromophenylazo-grafted polyhydroxy graphene oxide (PBPA-MHGO, 0.25 g).
[0070] It can be seen from Examples 1, 4, and 5 that when the molar ratio of p-bromoaniline to sodium nitrite is lower than 1:1.05, the diazotization reaction of p-bromoaniline is incomplete and the product quality is reduced; when the molar ratio is higher than 1:1.15, the product quality remains substantially unchanged, which results in a waste of sodium nitrite. Therefore, the following examples will be described according to a molar ratio of p-bromoaniline to sodium nitrite of 1:1.1.
[0071] Example 6.
[0072] (1) Add p-bromoaniline (1.03 g, 6 mmol) to a dilute hydrochloric acid solution (6 mL, 4 mol / L), heat to completely dissolve the p-bromoaniline, and then cool the solution in an ice-water bath (-3 to 0°C).
[0073] (2) Dissolve sodium nitrite (0.46 g, 6.6 mmol) in 4 mL of water to obtain an aqueous solution of sodium nitrite, slowly dropwise add the aqueous solution of sodium nitrite to the solution obtained in step 1, and stir in an ice-water bath for 30 minutes. Then add urea (10 mg, 0.2 mmol) to remove excess sodium nitrite, and continue stirring for 10 minutes to obtain a diazonium salt solution.
[0074] (3) Add polyhydroxy graphene oxide suspension (150 mL) into a three-necked flask, dissolve sodium bicarbonate (0.42 g, 5 mmol) and sodium carbonate (0.20 g, 2 mmol) in water (50 mL) to prepare an alkaline buffer solution to adjust the pH of the suspension, and place it in an ice water bath and stir. The molar ratio of p-bromoaniline to polyhydroxy graphene oxide is 200:1.
[0075] (4) The prepared diazonium salt solution was slowly added dropwise to the above suspension, and the mixture was stirred in an ice-water bath for 4 hours to carry out the coupling reaction. Dilute hydrochloric acid was added to remove the excess sodium bicarbonate and sodium carbonate until the pH value was 7, and then the temperature was raised to 50° C. and the mixture was stirred for 4 hours to remove the by-products.
[0076] (5) After the reaction is completed, the system is cooled to room temperature, filtered, washed with water, and vacuum dried at 80° C. for 48 hours to obtain the product p-bromophenylazo-grafted polyhydroxy graphene oxide (PBPA-MHGO, 0.22 g).
[0077] Example 7.
[0078] (1) Add p-bromoaniline (1.03 g, 6 mmol) to a dilute hydrochloric acid solution (6 mL, 4 mol / L), heat to completely dissolve the p-bromoaniline, and then cool the solution in an ice-water bath (5-8°C).
[0079] (2) Dissolve sodium nitrite (0.46 g, 6.6 mmol) in 4 mL of water to obtain an aqueous solution of sodium nitrite, slowly dropwise add the aqueous solution of sodium nitrite to the solution obtained in step 1, and stir in an ice-water bath for 30 minutes. Then add urea (10 mg, 0.2 mmol) to remove excess sodium nitrite, and continue stirring for 10 minutes to obtain a diazonium salt solution.
[0080] (3) Add polyhydroxy graphene oxide suspension (150 mL) into a three-necked flask, dissolve sodium bicarbonate (0.42 g, 5 mmol) and sodium carbonate (0.20 g, 2 mmol) in water (50 mL) to prepare an alkaline buffer solution to adjust the pH of the suspension, and place it in an ice water bath and stir. The molar ratio of p-bromoaniline to polyhydroxy graphene oxide is 200:1.
[0081] (4) The prepared diazonium salt solution was slowly added dropwise to the above suspension, and the mixture was stirred in an ice-water bath for 4 hours to carry out the coupling reaction. Dilute hydrochloric acid was added to remove the excess sodium bicarbonate and sodium carbonate until the pH value was 7, and then the temperature was raised to 50° C. and the mixture was stirred for 4 hours to remove the by-products.
[0082] (5) After the reaction is completed, the system is cooled to room temperature, filtered, washed with water, and vacuum dried at 80° C. for 48 hours to obtain the product p-bromophenylazo-grafted polyhydroxy graphene oxide (PBPA-MHGO, 0.21 g).
[0083] It can be seen from Examples 1, 6 and 7 that when the reaction temperature is lower than 0°C, the diazotization reaction rate is slow and the reaction yield is reduced; when the reaction temperature is higher than 5°C, the decomposition of the diazonium salt is accelerated, which also reduces the yield.
[0084] Example 8.
[0085] (1) Add p-bromoaniline (1.03 g, 6 mmol) to a dilute hydrochloric acid solution (6 mL, 4 mol / L), heat to completely dissolve the p-bromoaniline, and then cool the solution in an ice-water bath (0-5°C).
[0086] (2) Dissolve sodium nitrite (0.46 g, 6.6 mmol) in 4 mL of water to obtain an aqueous solution of sodium nitrite, slowly dropwise add the aqueous solution of sodium nitrite to the solution obtained in step 1, and stir in an ice-water bath for 30 minutes. Then add urea (10 mg, 0.2 mmol) to remove excess sodium nitrite, and continue stirring for 10 minutes to obtain a diazonium salt solution.
[0087] (3) Add polyhydroxy graphene oxide suspension (150 mL) into a three-necked flask, dissolve sodium bicarbonate (0.42 g, 5 mmol) and sodium carbonate (0.20 g, 2 mmol) in water (50 mL) to prepare an alkaline buffer solution to adjust the pH of the suspension, and place it in an ice water bath and stir. The molar ratio of p-bromoaniline to polyhydroxy graphene oxide is 200:1.
[0088] (4) The prepared diazonium salt solution was slowly added dropwise to the above suspension, and the mixture was stirred in an ice-water bath for 2 hours to carry out the coupling reaction. Dilute hydrochloric acid was added to remove the excess sodium bicarbonate and sodium carbonate until the pH value was 7, and then the temperature was raised to 50°C, and the mixture was stirred for 4 hours to remove the by-products.
[0089] (5) After the reaction is completed, the system is cooled to room temperature, filtered, washed with water, and vacuum dried at 80° C. for 48 hours to obtain the product p-bromophenylazo-grafted polyhydroxy graphene oxide (PBPA-MHGO, 0.21 g).
[0090] Example 9.
[0091] (1) Add p-bromoaniline (1.03 g, 6 mmol) to a dilute hydrochloric acid solution (6 mL, 4 mol / L), heat to completely dissolve the p-bromoaniline, and then cool the solution in an ice-water bath (0-5°C).
[0092] (2) Dissolve sodium nitrite (0.46 g, 6.6 mmol) in 4 mL of water to obtain an aqueous solution of sodium nitrite, slowly dropwise add the aqueous solution of sodium nitrite to the solution obtained in step 1, and stir in an ice-water bath for 30 minutes. Then add urea (10 mg, 0.2 mmol) to remove excess sodium nitrite, and continue stirring for 10 minutes to obtain a diazonium salt solution.
[0093] (3) Add polyhydroxy graphene oxide suspension (150 mL) into a three-necked flask, dissolve sodium bicarbonate (0.42 g, 5 mmol) and sodium carbonate (0.20 g, 2 mmol) in water (50 mL) to prepare an alkaline buffer solution to adjust the pH of the suspension, and place it in an ice water bath and stir. The molar ratio of p-bromoaniline to polyhydroxy graphene oxide is 200:1.
[0094] (4) The prepared diazonium salt solution was slowly added dropwise to the above suspension, and the coupling reaction was continued in an ice-water bath with stirring for 8 hours. Dilute hydrochloric acid was added to remove the excess sodium bicarbonate and sodium carbonate until the pH value was 7, and then the temperature was raised to 50°C, and stirring was continued for 4 hours to remove the by-products.
[0095] (5) After the reaction is completed, the system is cooled to room temperature, filtered, washed with water, and vacuum dried at 80° C. for 48 hours to obtain the product p-bromophenylazo-grafted polyhydroxy graphene oxide (PBPA-MHGO, 0.24 g).
[0096] It can be seen from Examples 1, 8, and 9 that when the coupling reaction time is less than 4 hours, the coupling reaction is incomplete and the reaction yield is low; when the coupling reaction time is more than 7 hours, the unreacted diazonium salt gradually decomposes, the reaction does not continue, and the yield remains essentially unchanged.
[0097] Example 10.
[0098] (1) Add p-chloroaniline (0.77 g, 6 mmol) to a dilute hydrochloric acid solution (6 mL, 4 mol / L), heat to completely dissolve the p-chloroaniline, and then cool the solution in an ice-water bath (0-5°C).
[0099] (2) Dissolve sodium nitrite (0.46 g, 6.6 mmol) in 4 mL of water to obtain an aqueous solution of sodium nitrite, slowly dropwise add the aqueous solution of sodium nitrite to the solution obtained in step 1, and stir in an ice-water bath for 30 minutes. Then add urea (10 mg, 0.2 mmol) to remove excess sodium nitrite, and continue stirring for 10 minutes to obtain a diazonium salt solution.
[0100] (3) Add polyhydroxy graphene oxide suspension (150 mL) into a three-necked flask, dissolve sodium bicarbonate (0.42 g, 5 mmol) and sodium carbonate (0.20 g, 2 mmol) in water (50 mL) to prepare an alkaline buffer solution to adjust the pH of the suspension, and place it in an ice water bath and stir. The molar ratio of p-chloroaniline to polyhydroxy graphene oxide is 200:1.
[0101] (4) The prepared diazonium salt solution was slowly added dropwise to the above suspension, and the mixture was stirred in an ice-water bath for 4 hours. Dilute hydrochloric acid was added to remove excess sodium bicarbonate and sodium carbonate until the pH value reached 7, and the temperature was then raised to 50°C, and the mixture was stirred for 4 hours to remove by-products.
[0102] (5) After the reaction is completed, the system is cooled to room temperature, filtered, washed with water, and vacuum dried at 80° C. for 48 hours to obtain the product p-chlorophenylazo-grafted polyhydroxy graphene oxide (PCPA-MHGO, 0.28 g).
[0103] Example 11.
[0104] (1) Add p-trifluoromethylaniline (0.97 g, 6 mmol) to a dilute hydrochloric acid solution (6 mL, 4 mol / L), heat to completely dissolve the p-trifluoromethylaniline, and then cool the solution in an ice-water bath (0-5°C).
[0105] (2) Dissolve sodium nitrite (0.46 g, 6.6 mmol) in 4 mL of water to obtain an aqueous solution of sodium nitrite, slowly dropwise add the aqueous solution of sodium nitrite to the solution obtained in step 1, and stir in an ice-water bath for 30 minutes. Then add urea (10 mg, 0.2 mmol) to remove excess sodium nitrite, and continue stirring for 10 minutes to obtain a diazonium salt solution.
[0106] (3) Add polyhydroxy graphene oxide suspension (150 mL) into a three-necked flask, dissolve sodium bicarbonate (0.42 g, 5 mmol) and sodium carbonate (0.20 g, 2 mmol) in water (50 mL) to prepare an alkaline buffer solution to adjust the pH of the suspension, and place it in an ice water bath and stir. The molar ratio of trifluoromethylaniline to polyhydroxy graphene oxide is 200:1.
[0107] (4) The prepared diazonium salt solution was slowly added dropwise to the above suspension, and the mixture was stirred in an ice-water bath for 4 hours. Dilute hydrochloric acid was added to remove excess sodium bicarbonate and sodium carbonate until the pH value reached 7, and the temperature was then raised to 50°C, and the mixture was stirred for 4 hours to remove by-products.
[0108] (5) After the reaction is completed, the system is cooled to room temperature, filtered, washed with water, and vacuum dried at 80° C. for 48 hours to obtain the product trifluoromethylphenylazo-grafted polyhydroxy graphene oxide (PTFMPA-MHGO, 0.37 g).
[0109] Test example 1.
[0110] FT-IR spectrum analysis: Figure 2 The infrared spectra of the products PBPA-MHGO, PCPA-MHGO and PTFMPA-MHGO of Examples 1, 10 and 11 are shown in Figure 1. The infrared spectra at 1488, 1486 and 1480 cm -1 The absorption peaks are attributed to the stretching vibration of CN, located at 1632, 1623 and 1615 cm -1 The absorption peak is attributed to the stretching vibration of N=N, indicating the presence of phenylazo groups in the product.
[0111] Test case 2.
[0112] X-ray diffraction pattern analysis: Figure 3 The X-ray diffraction patterns of the products PBPA-MHGO, PCPA-MHGO, and PTFMPA-MHGO of Examples 1, 10, and 11 are shown in Figure 1. As shown in the figure, compared with MHGO polyhydroxy graphene oxide, the products have new diffraction peaks at 2θ=9.76°, 9.28°, and 9.24°, corresponding to interlayer spacings of 0.91nm, 0.95nm, and 0.96nm, respectively. This is because the grafting of phenylazo groups onto the MHGO surface enlarges the average distance between adjacent layers.
[0113] Test case 3.
[0114] Wave absorption performance test: The materials obtained in Examples 1, 10, and 11 were uniformly mixed with paraffin in a mass ratio of 2:3, and then pressed into a ring-shaped test sample with an outer diameter of 7.0 mm, an inner diameter of 3.00 mm, and a thickness of 2.00 mm. The sample was connected to a vector network analyzer, and the wave absorption performance spectrum and electromagnetic impedance matching spectrum were tested in the frequency range of 2-18 GHz.
[0115] Test results such as Figure 4 As shown, Figure 4 (ac) in the middle is the reflection loss and frequency correlation spectrum of the annular test sample. It can be seen that the minimum reflection loss of the polyhydroxy graphene oxide material grafted with azo groups exceeds the performance requirement of the minimum reflection loss of -10dB defined by the absorbing material. When the thickness is 2.0mm, PBPA-MHGO reaches a minimum reflection loss of -21.64dB at 16.24GHz, and the effective bandwidth is 6.92GHz. When the thickness is 2.5mm, PCPA-MHGO reaches a minimum reflection loss of -38.32dB at 13.26GHz, and the effective bandwidth is 5.91GHz. When the thickness is 3.5mm, PTFMPA-MHGO reaches a minimum reflection loss of -51.17dB at 10.24GHz, and the effective bandwidth is 4.84GHz.
[0116] Figure 4 (df) is the impedance matching and frequency dependence spectrum of the ring test sample. When the ratio of input impedance to free space impedance |Z in The closer / Z0| is to 1, the more the material can absorb electromagnetic waves and dissipate them internally. As shown in the figure, when the thickness is 2.0 mm, the electromagnetic impedance of PBPA-MHGO is 0.82 at 16.24 GHz; when the thickness is 2.5 mm, the electromagnetic impedance of PCPA-MHGO is 1.03 at 13.26 GHz; when the thickness is 3.5 mm, the electromagnetic impedance of PTFMPA-MHGO is 0.99 at 10.24 GHz. Therefore, the grafted phenylazo group can effectively adjust the impedance matching of graphene-based materials.
Claims
1. A polyhydroxy graphene oxide-based material grafted with a phenylazo group, characterized in that: The preparation method of the material is as follows: Step 1, adding an aniline compound to a dilute hydrochloric acid solution, heating until completely dissolved, and then cooling under low temperature conditions; Step 2, adding a sodium nitrite solution dropwise to the solution prepared in step 1, adding urea to remove excess sodium nitrite after sufficient reaction under low temperature conditions, stirring, and obtaining a diazonium salt; Step 3, taking the polyhydroxy graphene oxide suspension, and adjusting the pH to 8-10 with an alkaline buffer; Step 4, adding the diazonium salt prepared in step 2 to the suspension prepared in step 3, and continuing stirring at low temperature to carry out coupling reaction; Step 5, after the coupling reaction is completed, filtering, washing, and vacuum drying are performed to obtain a polyhydroxy graphene oxide-based material grafted with a phenylazo group; In the above steps, the molar ratio of the aniline compound, sodium nitrite and dilute hydrochloric acid is 1:(1.05-1.15):(2.5-5.5); the molar ratio of the aniline compound to the polyhydroxy graphene oxide is 200:
1.
2. The polyhydroxy graphene oxide-based material grafted with phenylazo groups according to claim 1, wherein in step 1, the aniline compound is p-bromoaniline, p-chloroaniline or p-trifluoromethylaniline.
3. The polyhydroxy graphene oxide-based material grafted with a phenylazo group according to claim 2, wherein: The low temperature condition is 0-5°C ice water bath.
4. The polyhydroxy graphene oxide-based material grafted with a phenylazo group according to claim 3, wherein: In step 4, the coupling reaction time is 4 to 7 hours.
5. The polyhydroxy graphene oxide-based material grafted with phenylazo groups according to claim 4, wherein in step 1, the concentration of the dilute hydrochloric acid is 4 to 6 mol / L.
6. The polyhydroxy graphene oxide-based material grafted with a phenylazo group according to claim 1, wherein in step 3, the polyhydroxy graphene oxide suspension is prepared by the following method: 1) dispersing graphene oxide in DMSO, adding manganese acetate as a catalyst, stirring to form a suspension, and adjusting the pH to 4 with a dilute hydrochloric acid solution; 2) irradiating the suspension with ultraviolet light for 8 days, adding ZnO and isopropanol, and continuing to irradiate under ultraviolet light for 8 days to obtain a polyhydroxy graphene oxide suspension.
7. The polyhydroxy graphene oxide-based material grafted with phenylazo groups according to claim 5, wherein: In step 3, the alkaline buffer is a buffer prepared from sodium carbonate and sodium bicarbonate.
8. The polyhydroxy graphene oxide-based material grafted with a phenylazo group according to claim 1, wherein in step 4, an appropriate amount of dilute hydrochloric acid is added after the coupling reaction, the temperature is raised and stirring is continued, and excess alkaline buffer is removed until the pH value reaches 7; then the temperature is raised to 50°C, stirring is continued for 4 hours, and by-products are removed.
9. The polyhydroxy graphene oxide-based material grafted with phenylazo groups according to claim 1, wherein in step 5, the vacuum drying is performed at a temperature of 80 to 120°C for 48 hours.
10. Use of the polyhydroxy graphene oxide-based material grafted with phenylazo groups according to any one of claims 1 to 9 in microwave absorption.
Citation Information
Patent Citations
Preparation method of graphene / polyaniline binary wave absorbing material
CN109456478A
Method for modifying water-based lubricating fluid with wood flour-soybean lecithin
CN110791365A
Synthesis method of p-cyanobenzene azo grafted graphene oxide
CN116075144A
Super-flexible high thermal conductive graphene film and preparation method therefor
WO2017128648A1
Hybrid adhesive composition for blocking electromagnetic waves, method for producing same, and hybrid adhesive film for blocking electromagnetic waves
WO2022054979A1